Optimalisasi Self Efficacy Pasien Chronic Kidney Disease (CKD)melalui Edukasi Pembatasan Caira - Akbar, Akbar Asfar; sudarman; Wan Sulastri Emin; Brajakson Siokal; Wa Ode Sri Asnaniar; Yusrah Taqyiah; Fatma Jama; Suhermi; Samsualam (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2022)
Chronic kidney disease is a clinical condition characterized by a progressive and irreversible decline in kidney function, requiring appropriate renal replacement therapy in the form of kidney transplantation or dialysis. The prevalence of chronic kidney disease (CKD) is increasing, as is the case with chronic kidney failure patients undergoing hemodialysis therapy. Self-efficacy is a belief that determines how a person thinks, motivates himself and decides to perform a behavior to achieve the desired goal. Self efficacy affects the quality of life of CKD patients undergoing hemodialysis. Regulation of fluid intake is very important and can affect the increase in Interdialytic Waight Gain (IDWG). Weight gain is a major problem in patients undergoing hemodialysis therapy of more than 4 kg. During interviews with patients undergoing therapy, it turned out that there were still many who had not done fluid restriction as recommended. The method used in community service activities is by lectures/counseling, discussion and question and answer. The results of the dedication showed that the education participants listened well and understood the importance of fluid restriction in patients with CKD. The results of this activity increase the patient's understanding or self-efficacy based on the results of pre-test and post-test evaluations regarding fluid restriction. Keywords: Chronic Kidney Disease, Hemodialysis, Self Efficacy